Prevalence and Associated Factors of Depression and Anxiety in Adolescents Residing in Malay-operated Non-government-run Sheltered Homes in Selangor, Malaysia - Firdaus Mukhtar,; Wai-Eng Ding,; Munn Sann Lye,; Hamidin Awang; Khadeeja Munawar (UPM Press, 2024)
Indexed by ERA/MyCite